Reforming printing : Syon Abbey's defence of orthodoxy, 1525-1534 - Da Costa, Alexandra, 1982- (Oxford : Oxford University Press, 2012)
This text investigates how Syon Abbey responded to the religious turbulence of the 1520s and 1530s. It examines the 11 books 3 brothers had printed during this period and argues that the Bridgettines used vernacular printing to engage with religious and political developments that threatened their understanding of orthodox faith.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Keywords: Bonde, William, -- fl. 1526-1527 -- Criticism and interpretation; Fewterer, John -- Criticism and interpretation; Whitford, Richard, -- fl. 1495-1555? -- Criticism and interpretation; Bridgettines -- England -- London -- History -- 16th century; Syon Abbey (Isleworth, London, England) -- History -- 16th century; Catholic Church -- Apologetic works -- History and criticism; Religion and religious literature -- England -- History -- 16th century; Early printed books -- 16th century; Transmission of texts -- England -- History -- 16th century; England -- Church history -- 16th century